Xenotransplante ovariano caprinos: efeitos da vitrificação, do sexo e da linhagem receptora - Pimentel, Muriel Magda Lustosa (Universidade Federal Rural do Semi-Árido, 2018)
The ovarian tissue xenotransplantation represents a promising tool to investigate the reproductive potential in different domestic mammals, however its applicability in goats still needs to be more studied. The aim of this study was to evaluate the use of transplanted goat ovarian tissue in two immunosuppressed mice (C57BL/6 SCID and BALB/c Nude). For the first experiment, ovaries of goat fetuses were collected after the slaughter of their mother, fragmented and destined to the control evaluation, to fresh xenotransplantation (XF) and xenotransplantation after cryopreservation (XC). Five recipients from each line were used for fresh xenotransplantation and 10 animals from each line for cryopreserved xenotransplantation. The recipient mice were euthanized after 65 days of post-surgery, transplants being collected for macro and microscopic assessment and blood was collected via intracardiac puncture for measurement of estradiol. For the second experiment, ovarian fragments (1.0 mm³) of six young goats were xenotransplanted immediately after harvesting to ten recipients of each lineage. After 65 days of xenotransplantation, the animals were euthanized and the transplants evaluated for macroscopic characteristics, histologic sections and oocyte development in vitro. Additionaly, blood plasma was recovered from the recipients for the quantification of estradiol levels and renal and hepatic biochemical analyzes. In the first experiment, it was observed that regardless of the lineages, all the recipients presented return to ovarian activity with complete estrous cycle after XF and 80% after XC. Follicles were observed at all stages of development and without morphological changes. The volume density and total vessel surface observed in the transplants were different (p <0.01) between the XF and XC groups. The dose of 17β-estradiol in the recipients did not differ (p <0.05) between the treatments. In the second experiment, we observed preantral and antral follicles without morphological changes in the recovered transplants . Moreover, in a BALB/c Nude recipient, an oocyte recovered and submitted to maturation, fertilization and in vitro culture, without however presenting embryonic development. No differences were observed in the biochemical dosages but there were differences in 17β-estradiol concentration between the C57BL6 SCID and BALB/c Nude and their respective controls. It can be concluded that it is possible to activate the preantral follicles of the ovaries of goats by optimizing the use and conservation of goat germplasm in immunosuppressed mice of the C57BL / 6 SCID and BALB / c Nude, gonadectomized and independently of gender
Keywords: Fetal; Cabras; Vitrificação; Germoplasma; Fetal; Goats; Vitrification; Conservation of germplasm; CIENCIAS AGRARIAS::MEDICINA VETERINARIA